Major Trade Trends in East Asia : What are their Implications for Regional Cooperation and Growth? - Ng, Francis; Yeats, Alexander (World Bank, Washington, DC, 2014)
This study's empirical findings have positive implications for further efforts to expand East Asian regional trade and cooperation initiatives. Since the mid-1980s regional intra-trade has grown at a rate roughly double that of world trade, and at a rate far higher than the intra-trade of the North America Free Trade Agreement (NAFTA) member countries or the European Union. Evidence based on intra-industry trade ratios or statistics on international production sharing show economic linkages and the interdependence of East Asian economies have considerably strengthened over the past two decades. On a global scale, East Asia (excluding Japan) now originates 19 percent of world trade, which is approximately the same share as the NAFTA member countries.